DEMOGRAPHIC BEHAVIOR OF THE DAGESTAN FAMILY: STATE AND TENDENCIES - Zagirova, E M (History, Archeology and Ethnography of the Caucasus, 2016)
The article deals with the peculiarities of demographic behavior of Dagestan peoples and the focus is on the analysis of the birth rate in the republic as well as on complexity and contradictions of the modern family and demographic policy. Basing on the results of the sociological survey, the author of the article presents the family pattern existing in mass consciousness of Dagestan peoples, their understanding of the institution of the family, attitude to voluntarily childless married couples. The author emphasizes the necessity to preserve traditional family relationships while preserving the national traditions and customs of the nationality, which nowadays are fully observed neither at the macro level nor at the micro level, within a particular family.
Keywords: demographic problems; low birth rate; demographic policy; Dagestan peoples; demographic processes